A violência obstétrica na percepção de parturientes e profissionais de saúde na cidade de Manaus: análise sob uma perspectiva figuracional - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
From the academic and professional trajectory, interest in the study of symbolic representations of obstetric violence emerged from the perception of health professionals and parturients, analyzed through the Figurational Sociology, by Norbert Elias. The study under the theme "Obstetric violence in the perception of parturients and health professionals in the city of Manaus: analysis from a figurational perspective" started from an interdisciplinary approach in the area of human sciences, with a sociological and historical look at obstetric violence in Brazil and in the Brazilian Amazon. The study was developed within a qualitative approach, without neglecting quantitative aspects, through Comprehensive Sociology, it sought to: a) understand obstetric violence in the perceptions of parturients and health professionals from a figurational perspective; b) identify the psychosocial implications of obstetric violence; and c) describe the practices of coping with and eradicating obstetric violence in Amazonas. The problematizing question dealt with: obstetric violence as a social fact that has a character of exteriority in relation to individual consciences (discourse, practices), exerting a coercive force? According to the lucid reflection on the meaning of work, the study was carried out bringing the perspective of comprehensive sociology, in which a brief analysis of the theoretical construction on the representation of obstetric violence as a social phenomenon in expansion throughout history was carried out, the changes that shape modern society and its apparatus of surveillance and social control. Based on the method of discourse analysis, the phenomenon of violence was described, represented through the figuration in the power relationship between health professionals and parturients, in which it was considered that the city of Manaus is active in the fight and resistance against obstetric violence, however, the implementation of public policies still requires specific planning in the appropriate departments, with master programs or equivalent, with budget, deadlines, persons in charge, indicators, monitoring, evaluation and social control.
Obstetric violence in the perception of parturients and health professionals in the city of Manaus: analysis from a figurational perspective
Keywords: Violência em mulheres; Parto Humanizado; Parto - Aspectos psicológicos; CIENCIAS HUMANAS; Violência Obstétrica; Implicações Psicossociais; Figuração; Processo Civilizador; Parturientes